The In Vitro Anti-Diabetic Activity of Lime Peels (Citrus amblycarpa (Hassk.) Ochse) - Gempita cahya aulia tambunan; Aparna dutt; sayra nadhifa; firdha amelia; ermi girsang (Universitas Nahdlatul Ulama Surabaya, 2020)
There are various potential natural anti-diabetic drugs; one of them is lime peel or Citrus amblycarpa. This study was aimed to explore the anti-diabetic activity and phytochemical content of lime peels. This study was an experimental study that used the post-test only control group design. The lime peels that were collected from the Berastagi fruit market in Medan, North Sumatera were extracted using 70% ethanol by maceration methods. The phytochemical screening identified the presence of phenolic, steroid/triterpenoid, terpenoid, saponin, flavonoid, tannin, and alkaloid. Meanwhile, the anti-diabetic activity of lime peels was evaluate using the α-glucosidase enzyme that was gotten from Saccharomyces cerevisiae by α-glucosidase enzyme inhibition methods. Percent of inhibition was express as Mean ± SD and analyzed by One Way ANOVA, Tukey HSD Post Hoc Test, and followed by linear regression. The result of this study showed that there is a significant difference in percentage inhibition α-glucosidase enzyme in each concentration, and it had an IC50 Value amount of 125.93 ± 9.14 µg/mL. The phytochemical content of the lime peels was flavonoid, phenol, steroid/triterpenoid, and alkaloid. Hence, the lime peel has anti-diabetic activity by inhibition of the α-glucosidase enzyme.